Strategies for Indonesian Language Conservation in the Mindanao Diaspora: Educational and Cultural Identity Perspectives at the Indonesian School of Davao, Philippines - Riski, Yunia Tiara; Huda, Muhammad; Gunansyah, Ganes; Nasution, Nasution (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Language conservation is a vital part of preserving cultural identity, particularly within diaspora communities living in multicultural environments. This study aims to describe the strategies for conserving the Indonesian language implemented at the Indonesian School of Davao (Sekolah Indonesia Davao/SID), Philippines, and to examine the perspectives, expectations, and beliefs of stakeholders regarding language preservation as an element of national identity. The research also explores the gap between the ideal definition of language conservation and the actual use of the Indonesian language in the daily lives of the diaspora community, especially within the Consulate General of the Republic of Indonesia (KJRI) in Davao City and SID. A qualitative approach was employed using a case study method. Informants were selected purposively, including the deputy head of curriculum, deputy head of student affairs, dormitory supervisors, Indonesian language teachers, students, and staff from the Socio-Cultural Affairs Division (Pensosbud) of KJRI Davao City. Data collection techniques included in-depth interviews, observation, and documentation, which were then analyzed thematically. The findings indicate that language conservation at SID is carried out through curricular, regulatory, and cultural strategies, supported by the KJRI through the Basic Indonesian Knowledge Course (Kursus Pengetahuan Dasar Indonesia/KPDI). However, there is a noticeable gap between the ideal program and actual practice, as Indonesian is not yet fully used in the informal domains of the community. This study recommends the need for more contextual strategies and the development of culturally responsive learning materials based on the diaspora experience to support sustainable language preservation.